2022
DOI: 10.1029/2022wr031947
|View full text |Cite
|
Sign up to set email alerts
|

Red Noise in Steady‐State Multiphase Flow in Porous Media

Abstract: The flow of multiple fluids through a rock is a dynamic process involving fluid-fluid-rock interactions over multiple spatial and temporal scales. For instance, to understand the trapping of CO 2 underground, research spans from the sub mm-scale of high-resolution X-ray imaging experiments to observe pore scale phenomena

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…However, in experiment H, it matched only the f w = 0.9 case, which had an intermittency volume of 2.6%. For f w = 0.7 and 0.5, with intermittency volumes around 1.5%, the power associated to the longer timescales was significantly below red noise scaling, and thus differed from mm-scale observations by Spurin et al (2022). Since lower frequencies relate to larger sized fluid redistribution events, this may be further evidence for the need to study multiphase dynamics at the core-scale rather than in smaller samples.…”
Section: Representative Elementary Volumementioning
confidence: 85%
See 2 more Smart Citations
“…However, in experiment H, it matched only the f w = 0.9 case, which had an intermittency volume of 2.6%. For f w = 0.7 and 0.5, with intermittency volumes around 1.5%, the power associated to the longer timescales was significantly below red noise scaling, and thus differed from mm-scale observations by Spurin et al (2022). Since lower frequencies relate to larger sized fluid redistribution events, this may be further evidence for the need to study multiphase dynamics at the core-scale rather than in smaller samples.…”
Section: Representative Elementary Volumementioning
confidence: 85%
“…Further research with more data points is needed to investigate the results presented here. (2) Spurin et al (2022) asserted that the longest time-scales in this spectrum correspond to repetitive filling of the largest intermittent pores. They showed that the gas connectivity changed for intermittency with a time scale of 8-10 minutes as gas ganglia repeatedly connected and disconnected, while the intermittent gas occupancy with shorter time scales (i.e.…”
Section: Representative Elementary Volumementioning
confidence: 96%
See 1 more Smart Citation
“…In recent work exploring fluctuations in pressure data, red noise was observed [66]. This observation implies a cascade of timescales, with the longer timescales correlating to larger events.…”
Section: Sampling Intervals and Their Impact On Dmdmentioning
confidence: 87%
“…Fractional flow experiments typically aim to achieve a "steady-state" at each fractional flow step, which means both the saturation and pressure drop become time-independent. However, clear pressure fluctuations can be found in many fractional flow experiments (Lin et al, 2018;Menke et al, 2022;Spurin et al, 2022;Zou et al, 2018), and also The experiments H 0.5 , M 0.9 and L 0.9 are selected because of the similar brine saturation in these three cases.…”
Section: Differential Pressure Measurements and Darcy's Lawmentioning
confidence: 99%